An Application of Digital Chemistry Telling (DCT) in the Basic Inorganic Chemistry Course to Improve Students’ Listening and Speaking Skills - Dyah Purwaningsih; Hari Sutrisno; Kun Sri Budiasih (LPPM UNY, 2011)
This study aims to design implementation strategies of DCT in the Basic Inorganic Chemistry course, develop an appropriate course to increase students’ active participation, and develop an evaluation system capable of providing an integrated assessment (both the learning process and outcomes) in the course. This study was conducted in two cycles for one semester during the academic year of 2008/2009. The implementation applied the principles of classroom action research consisting of four stages, i.e. planning, action implementation, observation, and reflection. The data were analyzed by grouping them into categories. The findings were as follows. Qualitatively, the classroom observations showed an increasing active participation of students, both in making the DCT and in conducting discussions in English. Quantitatively, the results of the observations on the learning activities showed an average value of 4 (scale 1-5) for several aspects of DCT.